2017
DOI: 10.4269/ajtmh.16-0628
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Dapsone Hypersensitivity Syndrome Among Chinese Patients with an Emphasis on Preventing Adverse Drug Reactions with Genetic Testing

Abstract: Dapsone is a bactericidal and bacteriostatic against Mycobacterium leprae, a causative agent of leprosy. Dapsone is also applied in a range of medical fields because of its anti-inflammatory and immunomodulatory effects. Dapsone hypersensitivity syndrome (DHS) is a rare yet serious adverse drug reaction (ADR) caused by dapsone involving multiple organs. We performed a systematic review of published articles describing dapsone-induced hypersensitivity syndrome, including all Chinese articles and the latest lite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 19 publications
3
34
0
3
Order By: Relevance
“…In addition to its use as an antibiotic in patients with leprosy and as primary prevention and prophylaxis in patients with AIDS, dapsone was also used for the treatment of chronic inflammatory dermatoses (see Supplementary Table S2 online). With the increasing use of dapsone in clinical practice, studies showed that the Asian population has a higher risk of developing dapsone-induced hypersensitivity reactions, with an incidence rate of more than 1% (Wang et al, 2017). In this study, we analyzed the clinical manifestations of dapsone SCAR in a cohort of eight patients who presented with clinical features characteristic of DRESS.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to its use as an antibiotic in patients with leprosy and as primary prevention and prophylaxis in patients with AIDS, dapsone was also used for the treatment of chronic inflammatory dermatoses (see Supplementary Table S2 online). With the increasing use of dapsone in clinical practice, studies showed that the Asian population has a higher risk of developing dapsone-induced hypersensitivity reactions, with an incidence rate of more than 1% (Wang et al, 2017). In this study, we analyzed the clinical manifestations of dapsone SCAR in a cohort of eight patients who presented with clinical features characteristic of DRESS.…”
Section: Discussionmentioning
confidence: 99%
“…According to a recent review of published epidemiologic studies with patients from Asia, Europe, the United States, Australia, and Africa, total DHS prevalence was estimated to be about 1.4% (Lorenz et al, 2012). In Chinese leprosy patients, the prevalence of DHS is estimated at about 1.5%, with a mortality of 9.6%, based on our latest systematic review (Wang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, HLA-B*13:01 has been reported to be a predictor for dapsone-induced, drug-hypersensitivity syndromes among patients with leprosy. 15 HLA-B*13:01 has also been found among the three main indigenous groups in Peninsular Malaysia, namely the Temuan, Jehai, and Kensiu, with the Kensiu peoples having the highest allele frequency. 16 Whether this holds true for the indigenous peoples of the state of Pahang, resulting in higher CADR rates among them, requires further pharmacogenomic studies.…”
Section: Discussionmentioning
confidence: 99%